THE BIRTH OF THE EARTH'S ATMOSPHERE: THE BEHAVIOUR AND FATE OF ITS MAJOR ELEMENTS - Javoy M. (My University, 1998)
The accretion of the major volatiles of the Earth is described in the frame of the integral Enstatite Chondrite model [Javoy, M., 1995. The integral Enstatite Chondrite model of the Earth. G.R. Lett., 22, 2219–2222.]. The accretion of the Earth–Moon system takes place inside an inner solar system dominated by EH type material, at temperatures ≥1000°C. A late evolution of that system brings back some unmodified CI material at the end of the accretion on the edge of the inner zone where the Earth resides. This is the cause of a late veneer deposit weighing ∼1.4 per mil of the Earth mass. Following this model the upper and lower mantle are decoupled and the volatile evolution concerns essentially the Upper Earth (UE) (upper mantle+crust+ocean–atmosphere) with negligible contributions from the lower mantle. The main features are the following: (a) the bulk of the primary reduced material, constituting more than 99.8% of the total mass of the planet brought an isotopically light component corresponding to 6% of the hydrogen, 48% of the carbon and 70% of the nitrogen of the UE. (b) the late veneer (7.5 per mil of the UE's, 1.4 per mil of the bulk Earth's mass) of CI (or cometary) composition supplied an isotopically heavy component of H and N corresponding to 94% of the hydrogen, 52% of the carbon and 30% of the nitrogen. (c) the availability of oxygen in the UE results first from the partial reduction of silicon during the upper mantle–lower mantle–core differentiation (Javoy, 1995) bringing ∼7.5% FeO in the upper mantle. Then, the extra oxidizing reservoir due to the CI veneer creates the right proportion of FeIII in that primarily FeII system and explains the current 2.5% Fe3+/Fe2+ presently observed in the upper mantle. (d) atmospheric radiogenic argon is derived essentially from the outgassing of the UE which contains ∼450 ppm of potassium. The present distribution of the major volatiles in the UE corresponds to a negligible supply from the lower mantle. Measured in units of the superficial reservoirs (oceans, atmosphere, crustal carbon), the contents of the upper mantle are the following: water: 0.21 ocean masses, nitrogen: ∼10 atmosphere masses, carbon: 5.4 crustal carbon masses. This corresponds to a very significant trapping of carbon and nitrogen by the mantle during the Earth's history, whereas water repartition stayed about unchanged and strongly favoured the superficial reservoir. That difference between carbon and water is due to the fact that the major part of subducted water from oceanic crust escapes via arc volcanism. There is another very significant difference between carbon and nitrogen; the present outgassing and subducting fluxes of carbon are both mass- and isotopically-equilibrated, whereas there is still a gross isotopic disequilibrium for nitrogen, with the large, isotopically-heavy, subducted flux still outweighing the small, isotopically-light, outgassed flux. This is due to the fact that while carbon and water are essentially incompatible components, nitrogen is a compatible element because of the presence of very stable mantle nitrides (probably osbornite) or of nitride ions substituting oxygen in silicates.